Resource reservation in automotive ethernet - Almeida, André Rodrigues (2014)
In recent years, automotive industry has undergone major changes, being able to highlight not only the growing development of electronic systems in increasingly and varied features and contexts, as well as to cope with its growing interaction between with the driver and the outside world. Due to the huge amount of traffic involved in these system communications, networking technologies used so far are starting to be less appealing and the industry began to consider alternatives, economically more competitive as is the case of Ethernet. The use of Ethernet technology in automotive domains faces some challenges, namely with time constraints compliance and well defined resource requirements. The emergence of AVB (Audio Video Bridging) protocols, is trying to tackle some of these problems of having dynamic Quality of Service management in automotive Ethernet networks. One example of such protocols is the signalling protocol (SRP Stream Reservation Protocol), which could be used for providing a resource reservation mechanism in an automotive Ethernet domain. To test the feasibility of such recent methods, simulation tools are of paramount importance. This work presents an implementation of the SRP (Stream Reservation Protocol) in Omnet++, taking into account some of its constraints. It is described the fundamental aspects of this model implementation, as well as some functional tests.